Epidemiology of West Nile Virus in the Eastern Mediterranean region: A systematic review. - Sana Eybpoosh; Mehdi Fazlalipour; Vahid Baniasadi; Mohammad Hassan Pouriayevali; Farzin Sadeghi; Abbas Ahmadi Vasmehjani; Mohammad Hadi Karbalaie Niya; Roger Hewson; Mostafa Salehi-Vaziri (Public Library of Science (PLoS), 2019)
BACKGROUND:West Nile Virus (WNV), a member of the genus Flavivirus, is one of the most widely distributed arboviruses in the world. Despite some evidence for circulation of WNV in countries summarized by the World Health Organization as the Eastern Mediterrian Regional Office (EMRO), comprehensive knowledge about its epidemiology remains largely unknown. This study aims to provide a concise review of the published literature on WNV infections in the Eastern Mediterranean Regional Office of WHO (EMRO). METHODOLOGY/PRINCIPAL FINDINGS:A systematic review of WNV prevalence studies on humans, animals and vectors in the EMRO region was performed by searching: Web of Science, Science Direct, Scopus, PubMed, Embase and Google Scholar. Finally, 77 citations were included, comprising 35 seroprevalence studies on general population (24460 individuals), 15 prevalence studies among patients (3439 individuals), 22 seroprevalence studies among animals (10309 animals), and 9 studies on vectors (184242 vector species). Of the 22 countries in this region, five had no data on WNV infection among different populations. These countries include Kuwait, Bahrain, Oman, Syria and Somalia. On the other hand, among countries with available data, WNV-specific antibodies were detected in the general population of all investigated countries including Djibouti (0.3-60%), Egypt (1-61%), Iran (0-30%), Iraq (11.6-15.1%), Jordan (8%), Lebanon (0.5-1%), Libya (2.3%), Morocco (0-18.8%), Pakistan (0.6-65.0%), Sudan (2.2-47%), and Tunisia (4.3-31.1%). WNV RNA were also detected in patient populations of Iran (1.2%), Pakistan (33.3%), and Tunisia (5.3% -15.9%). WNV-specific antibodies were also detected in a wide range of animal species. The highest seropositivity rate was observed among equids (100% in Morocco) and dogs (96% in Morocco). The highest seroprevalence among birds was seen in Tunisia (23%). In addition, WNV infection was detected in mosquitoes (Culex, and Aedes) and ticks (Argas reflexus hermanni). The primary vector of WNV (Culex pipiens s.l.) was detected in Djibouti, Egypt, Iran and Tunisia, and in mosquitoes of all these countries, WNV was demonstrated. CONCLUSIONS:This first systematic regional assessment of WNV prevalence provides evidence to support the circulation of WNV in the EMRO region as nearly all studies showed evidence of WNV infection in human as well as animal/vector populations. These findings highlight the need for continued prevention and control strategies and the collection of epidemiologic data for WNV epidemic status, especially in countries that lack reliable surveillance systems.